A case of abnormal hypertension and Takotsubo syndrome caused by adrenal hemostasis using an electric scalpel: a case report - Tsutomu Suzuki; Naoko Kubo; Kei Kamiutsuri (JA Clinical Reports)
Abstract Background Although intraoperative adrenal hemostasis by cauterization can cause abnormal hypertension, hemodynamic condition is usually normalized in a few minutes without any postoperative complications. We present a rare case of abnormal hypertension caused by adrenal hemostasis using an electric scalpel, which resulted in cardiac dysfunction: Takotsubo syndrome. Case presentation A 74-year-old woman received open hepatectomy for a hepatic tumor. During adrenal electrocauterization, abnormal hypertension and tachycardia suddenly occurred. Although the blood pressure returned to the baseline in a few minutes by nicardipine and landiolol, postoperative echocardiography revealed apical hypokinesis and basal hyperkinesis of the left ventricular wall with a decreased ejection fraction of 50%. Along with no coronary artery stenosis by CT angiography, a diagnosis of Takotsubo syndrome was made. Postoperative course was uneventful; ejection fraction increased to 69% with no obvious left ventricular wall asynergy at 1-month postoperative follow-up. Conclusions Adrenal cauterization during surgery may cause abnormal hypertension by release of excessive catecholamines, and potentially lead to Takotsubo syndrome. Anesthesiologists should be prepared to respond quickly to any unexpected changes in hemodynamics.